2016
DOI: 10.1159/000445006
|View full text |Cite
|
Sign up to set email alerts
|

Role of C-Reactive Protein Assessment as Early Predictor of Surgical Site Infections Development after Pancreaticoduodenectomy

Abstract: Background: Surgical site infections (SSIs) are extremely common in pancreatic surgery and explain its considerable morbidity and mortality, even in tertiary centers. Early detection of these complications, with the help of laboratory assays, improve clinical outcome. The aim of the present study is to evaluate C-reactive protein (CRP) diagnostic accuracy as early predictor of SSIs after pancreaticoduodenectomy (PD). Methodology: We considered 251 consecutive PD. We prospectively recorded preoperative clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
14
0
3
Order By: Relevance
“…Increasing evidence shows that a systemic inflammatory response following surgical trauma is associated with poor outcome in patients after surgery, and this was revealed by serum C-reactive protein and albumin [9, 16, 17]. There are some inflammation-based prognostic scores, such as the modified Glasgow Prognostic Score (mGPS), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), postoperative Glasgow Prognostic Score (poGPS), and CRP to albumin ratio (CAR), that predict outcomes for surgical patients [15, 1820].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that a systemic inflammatory response following surgical trauma is associated with poor outcome in patients after surgery, and this was revealed by serum C-reactive protein and albumin [9, 16, 17]. There are some inflammation-based prognostic scores, such as the modified Glasgow Prognostic Score (mGPS), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), postoperative Glasgow Prognostic Score (poGPS), and CRP to albumin ratio (CAR), that predict outcomes for surgical patients [15, 1820].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have already focused on predicting SSI based on electronic health records (EHRs), for example, by using patient demographics, past medical history, and surgical information [15]. In recent studies, ranging from model evaluation methods, such as ROC analysis [16, 17], to data-driven modelling approaches, such as linear regression models [1, 18, 19] and Support Vector Machines [20], the attention has shifted to results of blood tests before and after surgery. One of the main reasons being the ease and extent of this type of data.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have taken a classical (knowledge-based) approach and handcrafted features by setting cutoff values of CRP after the surgery, where the term of postoperative day (POD) is commonly used. For example, Angiolini et al [19] evaluated the diagnostic accuracy as an early predictor of SSIs after pancreaticoduodenectomy and showed that CRP on POD 3, with a cutoff of 17.27 mg/dl, predicted the postoperative course in 78.2% of patients, whereas a CRP cutoff of 14.72 mg/dl on POD 4 predicted the postoperative course in 80.2% of patients. A systematic review of studies on diagnostic value of CRP after major abdominal surgery for predicting SSI [21] showed that CRP > 15.9 mg/dl on POD 3 increases the risk of SSI [10].…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico precoz de estas complicaciones es importante para poder instaurar el tratamiento apropiado y disminuir la mortalidad. La proteína C reactiva (PCR) se ha considerado como un marcador válido para la detección de complicaciones inflamatorias posoperatorias en cirugía pancreática [3][4][5][6][7] ; sin embargo, la procalcitonina (PCT), que es un marcador más válido para la detección de infección 8 , no ha sido muy investigada en pacientes con cirugía pancreática y solo hay unos pocos artículos en los que se analice su utilidad en este sentido. Planteamos este estudio con el fin de analizar la relación entre los valores de PCR y PCT, en los primeros días de posoperatorio, y la aparición de infección intraabdominal posoperatoria (IIAP) después de una DPC en pacientes con cáncer de páncreas.…”
Section: Introductionunclassified